Qualitative temporal structure and performance in badminton competition - Rivas, F.; Ruiz-Pérez, L.-M.; Gómez, M.-A. (World Badminton Federation, 2017)
Badminton is a quick, complex and dynamic sport (both physically and mentally) in which each player tries to destabilize the opponent`s balance and in turn generate disorder, while trying to maintain its own stability and self-organization when leading the rallies (Chow, Seifert, Hérault, Chia and Lee, 2014). In fact, badminton is a sport of constant adaptation (Abian et al., 2014) and evolvolution due to its dynamical temporal structure. Specifically, Cabello et al. (2004) studied the time structure of badminton competition in tournaments of 5 different levels: junior national, junior international, senior national, senior international and world championships). The authors found, that the greater the level of the competition was the fewer the differences between men and women`s singles were. That is, unlike national and intermediate international tournaments (junior and senior), world-class level shows no significant differences in the total playing time, total work and rest times. In contrast, Abian et al. (2013), claim that under the current scoring system at the 2008 Beijing Olympic Games, men`s singles players significantly played longer matches, longer rallies, rest more between rallies, played more rallies per match and shots per rally at a higher frequency than the women`s singles players who have in turn a greater work density and percentage of time played. Assuming that Cabello et al.`s (2004) and Abian et al.`s (2013) studies match each other concerning the level of the competitors engaged in different top competitions they fail to prove how the quality of opposition may influence these findings and mask their interactive effects. Thus, the aim of the present study was to show that the both the temporal structure of badminton and the outcome, for both men and women are influenced by the relative quality between the players as well as other variables such as, match status, score and game period. It was hypothesised that the profiling technique that accounts for quality of opposition equation will solve any kind of controversy/discrepancy to yield proper results to be used for practical purposes. Additionally, we intend to generalize a new method to gather new qualitative and useful temporal information in badminton matches for all the levels of competition.